IMPLEMENTASI SISTEM PARKIR DENGAN MENGGUNAKAN TEKNOLOGI RFID (RADIO FREQUENCY IDENTIFICATION) - Muhamad Rizal; Kusnadi Kusnadi; Ridho Taufiq Subagio (Jurnal Digit, 2018)
Abstract Increasingly and increasingly advanced technology currently available, especially in the field of electronics and telecommunications. One of the rapidly growing technologies of use is Radio Frequency Identification (Radio Frequency Identifier) or commonly known as RFID. The use of RFID has been widely used in various fields, ranging from sports, transportation, inventory, identification, payment of toll fees without stopping, indicator of vehicle entry to a building, arranging access to vehicles in certain communities, campuses and airports, tracking books libraries, and tracking of valuable assets and the most widely used is in the security field. RFID (Radio Frequency Identification) is the process of identification of objects automatically by using radio transmitting frequency. This technology consists of two main components, namely RFID Reader and RFID Tag. RFID Reader serves as a reader of codes contained in RFID Tags, whereas RFID Tags are devices that store information that identifies objects and can be called transponders. One RFID implementation can be applied to parking systems that require accuracy and speed of object identification. This RFID implementation will provide time efficiency, and will realize the revolution in modern parking management. Parking system that became the object of research that is at the Surya Sumber Store is still using the manual way that the ticket is still on hand and as a proof of parking of motor vehicles. Parking system used today still has many drawbacks that are easily damaged, no doorstop and less efficient in the implementation. Keywords: RFID, implementation, system, parking, frequency